Molecular identification and pathogenicity of Rhizoctonia spp. from tobacco growing areas in northwestern Argentina - Mercado Cardenas, Guadalupe Eugenia; Galvan, Marta Zulema; Barrera, Viviana Andrea; Rodriguero, Marcela Silvina; Carmona, Marcelo Anibal; March, Guillermo Juan; Ramallo, Ana Carolina; Shew, H. David (2018)
In Argentina, more than 60 % of the tobacco crops are grown in the northwestern part of the country and where Rhizoctonia solani leads to a reduction in crop yield and quality. In this study, 35 isolates of Rhizoctonia were obtained from 32 tobacco fields in northwestern Argentina and characterized by both morphological and molecular approaches. Based on the variability in the ITS region, isolates were identified as R. solani (80 %), Waitea circinata var. zeae (Rhizoctonia zeae) (8 %) and binucleate Rhizoctonia (8 %). Most isolates of R. solani belonged to the anastomosis groups (AGs) AG 4 HG-I (44 %), AG 2-1 (41 %) and AG 4 HG-III (13 %). Isolates of binucleate Rhizoctonia belonged to AG-F and AG-P of Ceratobasidium sp. Morphological variability was higher within isolates of AG 2-1 and AG 4 HG-III than within those of AG 4 HG-I. Aggressiveness of the isolates towards tobacco seedlings was assessed in the greenhouse. Isolates of AG 2-1 were the most aggressive on leaves, causing target spot, whereas isolates of AG 4 HG-I were the most aggressive on stems and roots, causing damping-off.